Sexual Aggression Victimization and Perpetration among Male and Female College Students in Chile - Schuster, Isabell; Krahé, Barbara; Ilabaca Baeza, Paola; Muñoz-Reyes, José A. (Frontiers in Psychology, 2016)
Evidence on the prevalence of sexual aggression among college students is primarily based on studies from Western countries. In Chile, a South American country strongly influenced by the Catholic Church, little research on sexual aggression among college students is available. Therefore, the purpose of the present study was to examine the prevalence of sexual aggression victimization and perpetration since the age of 14 (the legal age of consent) in a sample of male and female students aged between 18 and 29 years from five Chilean universities (N = 1,136), to consider possible gender differences, and to study the extent to which alcohol was involved in the reported incidents of perpetration and victimization. Sexual aggression victimization and perpetration was measured with a Chilean Spanish version of the Sexual Aggression and Victimization Scale (SAV-S), which includes three coercive strategies (use or threat of physical force, exploitation of an incapacitated state, and verbal pressure), three victim-perpetrator constellations (current or former partners, friends/acquaintances, and strangers), and four sexual acts (sexual touch, attempted sexual intercourse, completed sexual intercourse, and other sexual acts such as oral sex). Overall, 51.9% of women and 48.0% of men reported at least one incident of sexual victimization, and 26.8% of men and 16.5% of women reported at least one incident of sexual aggression perpetration since the age of 14. For victimization only few gender differences were found, but significantly more men than women reported sexual aggression perpetration. A large proportion of perpetrators also reported victimization experiences. Regarding victim-perpetrator relationship, sexual aggression victimization and perpetration were more common between persons who knew each other than between strangers. Alcohol use by the perpetrator, victim, or both was involved in many incidents of sexual aggression victimization and perpetration, particularly among strangers. The present data are the first to provide a systematic and detailed picture of sexual aggression among college students in Chile, including victimization and perpetration reports by both men and women and confirming the critical role of alcohol established in past research from Western countries.